Application of UWB wireless MIMO connectivity inside modern aircraft - Al-Khateeb, Khalid A. Saeed; Hakak, Saqib Iqbal; Khan, Sheroz; Alam, A. H. M. Zahirul; Yaacob, Mashkuri; Shahid, Zeeshan (Institute of Electrical and Electronics Engineers, Inc., 2016)
Monitoring a large number of interacting sensors, actuators and controllers in sensitive locations simultaneously, requires efficient and fast network. Sophisticated computer controlled systems in modern aircrafts have become a necessity. Wired connectivity can be both awkward and hazardous. In this paper we propose wireless connectivity based on Impulse-Radio Ultra Wideband (IR-UWB) system. It is a promising technology for the exchange of high data rates in a limited space. It acts like a Personal Local Area Network (PLAN) suitable for limited space within an aircraft. The proposed scheme utilizes the novel pulse generator developed in these laboratories. The pulse shapes comply with the FCC regulations regarding power levels and spectral mask limitations. It mitigates interference effects with narrowband systems. The proposed scheme has been analyzed theoretically and implemented practically giving sound results. It has so far proved to be an excellent short-range communication technology in terms of cost, speed, power consumption and capacity. A practical system is designed and built, which is capable of operating in the Gbps range. The proposal is anticipated to open possibilities for further applications such as ships, control towers operating theaters, and any other application where a large number of peripherals are in interaction simultaneously. The UWB pulse generator produces pulses, which are portions of simple monocycle sine wave shapes in the GHz range. Results obtained through simulation and theoretical analysis show excellent and constant agreement with results obtained by experimental measurements.